THE EFFECT OF STORAGE FOR 14 DAYS IN ROOM TEMPERATURE AGAINST EXTERNAL AND INTERNAL QUALITY OF DUCK EGGS IN JIMBARAN REGION - M. A, Kunaifi; Wirapartha, M.; Wiyana, i K. A. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to determine the effect of storage for 14 days at room temperature on the external and internal quality of duck eggs in Jimbaran. The study was conducted in Jimbaran area and analysis of egg’s sample was carried out at the Poultry Laboratory, Animal Husbandry Departement, Udayana University for three weeks. The research design was using Completely Randomized Design (CRD) consisting of 3 treatments eggs without storage as a control (P1), 7 days of egg storage (P2), and 14 days (P3), each treatment using 6 replications. Variables observed based on external quality included egg weight and egg shape index, and internal quality included egg yolk, Haugh unit (HU), and egg pH. The results showed that egg HU at 14 days storage had an average of 7,88% significantly lower (P<0,05) than control and egg HU at 14 days storage had an average of 6,02% significantly lower (P<0,05) compared to 7 days storage. Egg HU control and 7 days storage statistics showed no significant difference (P>0,05). According to egg weight, egg shape index, egg yolk color, and egg pH for 7 days and 14 days storage treatment gave results that were not significantly different (P>0,05). Based on the results of the study it can be concluded that the storage of duck eggs for 7 days and 14 days at room temperature 28 0 C in Jimbaran region do not reduce egg weight, egg shape index, yolk color and egg pH, but storage of duck eggs for 14 days decreases the value of Haugh unit (HU). Duck eggs are still suitable for consumption for 14 days of storage with A egg grade.   Keywords : duck eggs, storage time, egg quality